Suspected Transverse Myelitis with Normal MRI and CSF Findings in a Patient with Lupus: What to Do? A Case Series and Systematic Review - Monahan RC (Dove Medical Press, 2020)
Rory C Monahan,1 Hannelore JL Beaart,1 Rolf Fronczek,2,3 Gisela M Terwindt,2 Liesbeth JJ Beaart-van de Voorde,1 Jeroen de Bresser,4 Margreet Kloppenburg,1,5 Nic JA van der Wee,6 Tom WJ Huizinga,1 Gerda M Steup-Beekman1,7 1Department of Rheumatology, Leiden University Medical Center (LUMC), Leiden, the Netherlands; 2Department of Neurology, LUMC, Leiden, the Netherlands; 3Sleep-Wake Center SEIN, Heemstede, the Netherlands; 4Department of Radiology, LUMC, Leiden, the Netherlands; 5Department of Clinical Epidemiology, LUMC, Leiden, the Netherlands; 6Department of Psychiatry, LUMC, Leiden, the Netherlands; 7Department of Rheumatology, Haaglanden Medical Center, The Hague, the NetherlandsCorrespondence: Rory C MonahanDepartment of Rheumatology, Leiden University Medical Center (LUMC), Leiden 2333 ZA, the NetherlandsTel +3171-5265762Fax +3171-5266752Email r.c.monahan@lumc.nlPurpose: To evaluate the use of immunosuppressive treatment, clinical outcome and diagnostic strategy in patients with systemic lupus erythematosus (SLE) presenting with clinical features of transverse myelitis (TM), but normal MRI of the spinal cord (sMRI) and normal cerebrospinal fluid (CSF) assessment, and to suggest a clinical guideline.Patients and Methods: All patients with SLE and clinical features compatible with (sub)acute TM visiting the NPSLE clinic of the LUMC between 2007 and 2020 were included. Information on baseline characteristics, investigations, treatment and outcomes was collected from electronic medical records. In addition, a systematic review of individual participant data was performed up to April 2020 in PubMed, Embase and Web of Science, identifying all patients with TM, SLE and sMRI assessment. Data regarding sMRI, CSF analysis, treatment and outcome were extracted, and outcome was compared between patients with normal sMRI and CSF (sMRI-/CSF-) and patients with abnormalities.Results: Twelve SLE patients with a clinical diagnosis of TM were identified: four sMRI-/CSF- and one sMRI- with CSF not available. All patients received immunosuppressive treatment, but outcome in sMRI-/CSF- patients was worse: no recovery (n=1) or partial recovery (n=3) compared to partial recovery (n=4) and (nearly) complete recovery (n=3) in MRI+ patients. The systematic literature review yielded 146 articles eligible for inclusion, 90% case reports. A total of 427 SLE patients with TM were identified, of which only four cases were sMRI-/CSF- (1%), showing no improvement (n=1), partial improvement (n=2) and complete recovery (n=1) after immunosuppressive treatment.Conclusion: Outcome in SLE patients presenting with clinically suspected TM with normal sMRI and CSF is less favorable, despite treatment with immunosuppressive therapy. Taking a functional neurological disorder into consideration may be helpful in order to start other therapeutic strategies. We suggest prescribing immunosuppressive treatment for a restricted period of time to evaluate its effect in cases where a functional disorder initially is considered unlikely.Keywords: lupus, neuropsychiatric, transverse myelitis, MRI, CSF